– The Behavior of the Algerian Consumer towards Purchasing Situation affecting his Protection – A field study in the state of Adrar - Al Ali, Boukmeish; Jelali, Ghaloon (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to identify the behavior of the Algerian consumer in purchasing situations that affect his protection. The study examined the views of a Convenience sample of (150) consumers consist of different categories in the state of Adrar. A (112) copies of questionnaires were properly filled and returned. In order to test the hypotheses, a Chi-Square statistical tool was used. The study found that The Algerian consumer acts assertively toward purchasing situation affecting his protection by protesting against the sellers of foodstuffs, meat and medicinal herbs.While he behaves passively toward sellers of foodstuffs, restaurant meals, semi-pharmaceuticals, vegetables and clothing. The results of this study also revealed that the socio-personal variables have no significant effect on the Algerian consumer towards purchasing situation affecting his protection.